Ответ:
при к = 7
Пошаговое объяснение:
Х + 4У = 5 ====> Y = ( 5 - X) : 4
2X - E = 1 ====> Y = 2X - 1
(5 - X):4 = 2X - 1
5 - X = 8X - 4
9X = 9
X = 1
Y = 2*1 - 1
Y = 1
(1; 1) ====> координата точки пересечения прямых
Подставим ( 1; 1) в уравнение у = кХ - 6
1 = к*1 - 6
к = 7
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
при к = 7
Пошаговое объяснение:
Х + 4У = 5 ====> Y = ( 5 - X) : 4
2X - E = 1 ====> Y = 2X - 1
(5 - X):4 = 2X - 1
5 - X = 8X - 4
9X = 9
X = 1
Y = 2*1 - 1
Y = 1
(1; 1) ====> координата точки пересечения прямых
Подставим ( 1; 1) в уравнение у = кХ - 6
1 = к*1 - 6
к = 7